Associations between the personal style of the therapist, empathy and theory of mind among Argentine psychotherapists - Tabullo, Ángel Javier (2023)
Fil: Tabullo, Ángel Javier. Pontificia Universidad Católica Argentina. Facultad de Humanidades y Ciencias Económicas; Argentina